2019
DOI: 10.1002/cpp.2382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mindfulness training on the default mode network in borderline personality disorder

Abstract: Patients with borderline personality disorder (BPD) present dysfunctions of the default mode network (DMN). Mindfulness training has proven effective to improve the symptoms of BPD. The present study examines the effect of mindfulness training on BPD symptomatology and DMN activity during the performance of a working memory task in patients with BPD. Sixty-five individuals with BPD were randomized to receive psychotherapy with either the mindfulness module of dialectical behavioural therapy (DBT-M) or with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
(51 reference statements)
2
36
0
Order By: Relevance
“…However, there was no posttreatment difference in default mode network activation or deactivation across both groups, a brain region associated with various cognitive processes such as introspection, envisioning the future, and self-reflective thought (25). There was also no significant correlation between BPD symptoms or mindfulness outcomes and activation/deactivation of the cluster at the medial occipital location extending bilaterally from the calcarine to the cuneus and superior occipital gyri (22). These particular findings highlight how specific components of DBT, including mindfulness and interpersonal effectiveness, may be uniquely associated with post-treatment changes in specific brain regions.…”
Section: Fmri Findingsmentioning
confidence: 86%
See 3 more Smart Citations
“…However, there was no posttreatment difference in default mode network activation or deactivation across both groups, a brain region associated with various cognitive processes such as introspection, envisioning the future, and self-reflective thought (25). There was also no significant correlation between BPD symptoms or mindfulness outcomes and activation/deactivation of the cluster at the medial occipital location extending bilaterally from the calcarine to the cuneus and superior occipital gyri (22). These particular findings highlight how specific components of DBT, including mindfulness and interpersonal effectiveness, may be uniquely associated with post-treatment changes in specific brain regions.…”
Section: Fmri Findingsmentioning
confidence: 86%
“…With regards to the anterior insula, while two studies found reduced activation in the anterior insula after DBT treatment among patients with BPD (17,21), one study found a significant increase in activation in the anterior insula (22). One study also found that reduced activity in the anterior insula was significantly correlated with BPD symptom improvement (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…therapy (DBT) specifically improves inattention and impulsivity, suggesting it may have utility as a targeted treatment among those high on Disinhibition(Carmona i Farrés et al, 2019;Soler et al, 2012). Conversely, interventions that seek to improve interpersonal communication and problem-solving (e.g., DBT's interpersonal effectiveness and emotion regulation modules) may be well-suited for those high in Antagonism, who often struggle to control emotional outbursts in social interactions (indeed, interpersonal effectiveness training is associated with improvements in emotion regulation; Carmona i Farrés et al, 2019).…”
mentioning
confidence: 99%